"What Race Do You Consider Yourself?": Factors Influencing Use of Color in Racial Self-Classification - Shannon N. Davis; Ruth Jackson; Christine Aicardi (Sociation Today, 2012)
The purpose of this paper is to examine the factors that predict how individuals, when given the opportunity, choose to racially self-classify. This paper examines responses from a nationally representative United States survey, where respondents could use any language they chose to respond to the question “What race do you consider yourself?” We determine the demographic characteristics that are correlated with responding with a color versus a racial group (e.g., Black versus African American), noting that educational attainment seems to be the key correlate of language choice. Respondents with children aged 6-12 are also more likely to self describe race using color while those with teenagers are less likely to self-describe using color. Implications of the findings are discussed.